Analisis komponen minyak atsiri daun nilam (Pogostemon cablin) lokal Pekanbaru menggunakan GC-MS - Teruna, Hilwan Yuda; Rahayu, Wiwit Nur (Pengurus Pusat Ikatan Apoteker Indonesia, 2021)
Pogostemon cablin or nilam Aceh is a patchouli oil producer plant that is widely cultivated in Indonesia because the quality of the essential oil produced is better than other types of Pogostemon. The purpose of this study was to extract the local patchouli oil of Pekanbaru and compare its chemical components with standard patchouli oil. The quality of the patchouli essential oil of local Pekanbaru was also analyzed based on the chemical components. The extraction method used in this research was hydrodistillation using Clevenger apparatus. Volatile oil vapor evaporated together with water vapor and passed through the condenser. The oil was characterized by its components by GC-MS. The results found that the concentration of patchouli alcohol was 31.13%, along with other compounds such as α-patchoulene, β-patchoulene, seychellene, α-bulnensene, and cyclosativene. The difference of patchouli oil of P. cablin grown in Pekanbaru with the standard patchouli oil was that the concentration of patchouli alcohol in the local patchouli oil of Pekanbaru was high with no α-guaiene, there was a cyclosativene instead. Based on this, the local patchouli oil of Pekanbaru has a fairly good quality and has the potential to be developed further.